Switching costs and consumer behaviour: Implications for telecommunications regulation - Xavier, Patrick; Ypsilanti, D. (Camford Publishing Ltd, 2008)
Purpose – This paper aims to examine the extent to which telecommunications consumers decide to switch and why. Design/methodology/approach – Results from surveys of consumer switching behaviour in a number of countries are examined to ascertain reasons for actual consumer decision making regarding switching. Findings – Implications for telecommunications regulation are considered. In essence, regulation should require that communications service providers ensure that switching is fast, cheap, predictable and reliable and that consumers are able to switch with minimum difficulty and delay. Practical implications – The ability and willingness to switch from one to another supplier of telecommunications and internet services are an important aspect in manifesting consumer empowerment. In turn, empowered consumers are important for sustainable competition. If consumers are inert and passive, suppliers will not be under pressure to deliver the potential benefits of competition. And it is empowered assertive consumers, able and willing to switch, who will exert pressure on suppliers to deliver these benefits. Thus, in making well-informed choices between suppliers, consumers not only benefit from competition but also initiate and sustain it. Originality/value – Insights from behavioural economics are incorporated in the analysis.